Young Children and Voice Search: What We Know From Human-Computer Interaction Research - Lovato, Silvia B.; Piper, Anne Marie (Frontiers in Psychology, 2019)
Young children are prolific question-askers. The growing ubiquity of voice interfaces (e.g., Apple’s Siri, Amazon’s Alexa), as well as the availability of voice input in search fields, now make it possible for children to ask questions via Internet search when they are able to speak clearly, but before they have learned to read and write, typically between 3 and 6 years of age. The prevalence of voice search makes it important to understand children’s changing conceptions of digital devices as a source of information and the role of technology-mediated question-asking in development. While limited research has focused on young children’s use of voice interfaces, reviewing two related bodies of literature sheds light on how this use might unfold. This paper brings together studies of how children look for information, and of how they perceive and understand the informational and social roles of technology, drawing on human-computer interaction research. We conclude by highlighting lines of questioning for future work on younger children’s interaction through voice search.